Low-Cost Active Power Filter Using Four-Switch Three-Phase Inverter Scheme - Mohamed Azab (Electricity)
Shunt active power filters (SAPFs) have been around for a long time. They improve the quality of a current drawn from the grid when feeding non-linear loads formed by old-fashioned power electronic converters such as uncontrolled and controlled rectifiers. Most SAPFs are implemented using the well-known six-switch three-phase inverter (SSTPI) topology. This paper investigates the capability of adopting the four-switch three-phase inverter (FSTPI) scheme to develop low-cost SAPFs, mainly for low-power ranges. The performance of the proposed SAPF using the FSTPI topology is compared with the conventional scheme of an SAPF formed by the six-switch three-phase inverter (SSTPI) topology. Qualitative and quantitative analyses are conducted. The performance of the proposed FSTPI-based SAPF is investigated under different loading conditions. The obtained results indicate the validity and effectiveness of the FSTPI scheme in improving the quality of currents drawn from the AC grid. The SAPF scheme investigated is also feasible and results in cost reduction when the SAPF power circuit is constructed with modern WBG devices, such as SiC-based MOSFETs, which are relatively expensive (approximately three times the price of the equivalent Si IGBTs).